Traditional and specific principles interrelation for forming future labour protection specialists’ professional activity safety culture - Albiltarova, Elviza (Professional Pedagogics, 2018)
The article is devoted to the high priority problem of labour protection specialists professional training. Statistical data on industrial injuries in enterprises and organizations of the Crimea have been analyzed. Special attention is focused on the significancy and importance of preventive measures to preclude the causes of industrial accidents and occupational diseases. The necessity of forming professional activity safety culture for future labour protection specialists is substantiated. It is concluded that this problem requires the search and development of new methodological approaches, didactic principles that constitute the scientific and methodological basis of the study.The article highlights the theoretical studies results on the problem of didactic principles application while training process. The author provides the detailed analysis of scientific research, scientists’ views regarding didactic principles classification and content. General didactic (scientific; systematic and consistent; polytechnic principle; professional orientation; humanization; culturological principle) and specific (taking into account educational integration processes in higher education; creating efficient learning environment; close relationship of education and safety culture training; inclusion into innovative activities; designing an individual educational pathways for forming safety culture of professional activity; systematic organization the process of professional work safety culture forming; promotion of healthy lifestyles) principles of forming professional activity safety culture for future labour protection specialists are defined and characterized. The conclusion is made on the need for further research that requires substantiation and analysis of conceptual approaches, organizational and pedagogical conditions for optimizing the system of forming professional activity safety culture for future labour protection specialists.
Keywords: vocational training; didactic training; principles professional activity; safety culture; labour protection specialist; labour protection methodology; professional activity